War on terror : fantasy and fiction behind the mythology of terrorist financing - Abdel Salam, El Fatih Abdullahi (IIUM Press, 2009)
Documentary evidence shows that the series of financial crackdowns initiated since 9/11 have had virtually no impact on terrorism. This is because these efforts are based on a fundamental misconception on how terrorism works. The financial warriors’ predisposition to stereotypes about “Arabs and their money” allowed unsubstantiated rumours–such as Bin Laden’s personal fortune of $300 million–to become established as facts. This study exposes the extent to which Washington policymakers simply transposed the template for the war on drugs on to the war on terror, despite the fact that terrorism is not a profit– driven enterprise. The collateral damage inflicted on organisations like Al-Barakaat, the Somali remittance network, wrongly accused of channeling money to the terrorists, and others are counter-productive as they dent the image of the US in the Muslim world.